Building Competencies for the Workplace: A Study on the Influence of Skill Development in Education - Venkatesh Sarvasiddhi, NVM Rao, Geetilaxmi Mohapatra (European Economic Letters (EEL), 2024)
This paper reviews and analyzes the literature on the effect of skill improvement on schooling on employment in India. The predominant goal of this review of research is to study the impact of talent improvement packages on performance in the Indian schooling gadget. It examines the concept of talent development in education, assesses the effectiveness of existing applications, and identifies demanding situations encountered throughout implementation. Comprehensive literature evaluations and bibliometric seek strategies are used to research and synthesize studies, reports, and related works. The findings highlight the significance of upgrading abilities in addressing employment challenges, bridging the space between instructional and enterprise wishes, and enhancing financial increase. It concludes by way of discussing the demanding situations confronted in implementing skills development applications and identifies strategies that can be used to overcome them and contribute to the present literature by imparting insights into the effect of skill development on career components in Indian education